Management Services for Building Permits at the Investment Service and One-Stop Service in Bolaang Mongondow Utara Regency - Haltin Bolota; Lisda Van Gobel; Jusrin Kadir (Formosa Journal of Applied Sciences, 2022)
This study aims to identify and describe the service for obtaining building permits (IMB) at the Investment and One-Stop Services Office in North Bolaang Mongondow Regency. Types of Qualitative research. Data analysis begins with the process of data reduction, data presentation, and drawing conclusions. The results of this study indicate that the service for managing building permits at the Investment Service and One-Stop Service in North Bolaang Mongondow Regency is not optimal and optimal, there are several problems, namely; socialization, service completion time, human resources (officers), PMPTSP service office facilities, especially building permits, so that needs to be addressed in order to provide more optimal service and meet community expectations.